IMPLEMENTATION OF COOPERATIVE STRATEGIES IN TEACHING ENGLISH TO JUNIOR HIGH SCHOOL - Nur Afifah Nabila Putri; Ahmad Husein; Emeliya Sukma Dara Damanik (PRIMACY Journal of English Education and Literacy, 2022)
Cooperative learning is a strategy that is often used in the teaching and learning process. In which the learning process is carried out in groups by students. In this case the students become more dominant than the teacher. The implementation of this strategy is also a reference to be more open between students with different genders, academic abilities, and different races. The methodology used is qualitative in writing. This paper contains learning strategies for students, especially junior high schools, where the implementation itself will provide variations for teachers in teaching and make students more creative in building their own knowledge.